PELATIHAN PEMBELAJARAN BAHASA INGGRIS BEREKUIVALENSI TOEFL BAGI GURU TINGKAT SMP - Sari Mubaroh; Muhammad Setya Pratama; Indah Riezky Pratiwi (Martabe : Jurnal Pengabdian Kepada Masyarakat, 2022)
This training aims to help partners, SMP Negeri 3 Sungailiat, in their efforts to improve the ability to master English for teachers. This training is designed and oriented towards the mastery of English equivalent to TOEFL. This activity lasted for 3 days with details of 2 days of material delivery through webinars and 1 day of face-to-face tests. The length of time required is related to the time allocation provided by the school so as not to interfere with PBM activities at the school. The training participants were 34 teachers (thirty-four). The success of this program can be seen from the excellent attendance response every day. The average TOEFL score achieved by the participants was with an average TOEFL score of 411, increasing from the results that had been achieved before. In addition, the results stated that 76% of participants felt helped by the training materials received. Thus, the goal of this training has been well achieved.